2019
DOI: 10.18502/ijph.v48i4.982
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mother-Infant Skin to Skin Contact after Birth on Third Stage of Labor: A Systematic Review and Meta-Analysis

Abstract: Background: One of the causes of postpartum hemorrhage is prolongation of third stage of labor. Mother-infant skin to skin contact (SSC) immediately after delivery is one of the non-pharmacological interventions to reduce this stage. Studies which assessed the effect of mother-infant SSC after delivery on duration of the third stage of labor reported controversial results on this issue. Therefore, this study investigated the effect of mother-infant SSC immediately after birth on the duration of third stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 12 publications
0
17
0
3
Order By: Relevance
“…18,20 During immediate and uninterrupted SSC, newborns exhibit a species-specific sequence of nine instinctive behaviors that lead to finding the breast and suckling. 21 SSC reduces the duration of the third stage of labor, ameliorating the risk of postpartum hemorrhage, 22 and may reduce maternal stress, anxiety, and pain during and after a cesarean. 7…”
Section: Introductionmentioning
confidence: 99%
“…18,20 During immediate and uninterrupted SSC, newborns exhibit a species-specific sequence of nine instinctive behaviors that lead to finding the breast and suckling. 21 SSC reduces the duration of the third stage of labor, ameliorating the risk of postpartum hemorrhage, 22 and may reduce maternal stress, anxiety, and pain during and after a cesarean. 7…”
Section: Introductionmentioning
confidence: 99%
“…Some studies stated that scin to scin care may be effective on decreasing the pospartum depression, improvement of mother and child bonding. It is also suggested that scin to scin care should bwe strated at early time as soon as possbile 48‐53 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results of this study and the Somali Demographic Health Survey [1], backed with evidence from the WHO/ UNICEF reports [10,12], support providing culturally tailored education and training for health staff on skin-toskin contact as the care model, emphasising the advantages of starting the practice immediately after birth. During the first hour, the baby, if left alone, crawls to the mother's nipple to suckle on his/her own [24,25]. The infant is guided by the mother's scent, voice and temperature.…”
Section: Discussionmentioning
confidence: 99%